Who gets promoted to the top? Nuanced personality and psychosocial trait differences in highly structured work environments: Evidence from German professional female athletes - Felix Krause; Ho Fai Chan; Sascha Leonard Schmidt; Dominik Schreyer; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
Despite a solid foundation of women's career progression research, the role of personality and psychosocial characteristics in explaining objective career success is not yet fully understood. Structural underrepresentation of female executives at board levels remains an issue in both Europe in general and Germany in particular. Today, two alternative perspectives on the role of gender and personality in career advancement prevail. On the one hand, the gender-invariant role demands perspective suggests that women in executive positions show agentic personality traits, whereas advocates of the changing leadership roles perspective argue in the opposite direction, emphasizing the benefits of distinct communal traits in today's changing environment. Analyzing data from 299 German athletes from different sports contexts, 159 of which are female, we investigated the unsolved labor market success puzzle of which personality, psychosocial, and cognitive characteristics are rewarded at the very top of the labor market pyramid for females versus males. Our results provide further support for the genderinvariant role demands perspective as the female athletes who made it to the highest possible ranks do not show many clearly distinguished attributes from their male peers, despite high core self-evaluation (CSES) scores, i.e., rather agentic traits like internal locus of control, selfesteem, and self-efficacy. Using survival analysis, we also find support for the gender-invariant role demands perspective in explaining the relative speed of male and female athletes' promotions to top positions. As our results are derived from within-sex competition, i.e., women compete with women, while men compete with men for the top ranked spots, it is particularly noteworthy that even in such settings the gender-invariant role demands perspective prevails. This implies that the numerous efforts of organizations to encourage women's career progression in recent years need to start addressing leadership requirement perceptions at the core to plant the seed for increased probability of women reaching top executive positions.
Keywords: 330; CAAS; CSES; objective career success; personality traits; promotion